Severe post-partum autoimmune hypothyroidism associated with a novel loss-of-function mutation in intracellular domain of human thyrotropin receptor - Bose, Arindam; Sharma, Norman; Hemvani, Nanda; Chitnis, Dhananjay S. (Medical Studies/Studia Medyczne, 2016)
Several loss-of-function TSHR gene mutations have been reported previously. In the present study, a mutation in exon 10 of the TSHR gene was studied. A 35-year-old mother of two children attended our hospital with symptoms of hypothyroidism after her second delivery. She had elevated levels of thyroid hormones including both the thyroid antibodies and those treated with L-thyroxine. In the present study, exon 10 of the TSHR gene of the patient was studied. Sequencing of exon 10 revealed a G to T transversion, resulting in a loss of function mutation changing glutamic acid 757 to stop codon, (E757Stop) in the intracellular domain of TSH receptor and also C to T transition, leading to no change in amino acid sequence (glycine to glycine at 753 amino acid position). We report a novel sporadic loss of function mutation in TSHR protein at codon 757 (E757Stop).